A adoção das parcerias público-privadas no sistema prisional como medida efetiva para reinserção social dos presos - Rostirolla, Luciano (Universidade Federal do Tocantins, 2016)
This course conclusion work is the result of research on the applicability of publicprivate partnerships within the Brazilian prison system, especially in the state of Tocantins. The monopoly of the punitive power state was a breakthrough, however, brought a great challenge to the penitentiary law and the area of public security, which is to ensure the dignity of the convict and compliance with the provisions in the Penal Execution Law. The Brazil today has 607,731 prisoners, and the system capacity is only 376,669 vacancies. In addition to overcrowding, the conditions of prisons around the country are depressing causing the state punish the re-educating twice: one for having committed the crime and another for having deprived their freedom. Public-private partnerships - PPP for the construction and management of prisons emerge as an alternative to improve the conditions of the prison system as a whole. Emerged in the US, the model predicts the demise of public service to a private partner for remuneration. This is not privatization, because the state only provides public service through a rigorous for a definite term management contract. It differs mainly of concession and permission models, as well as build and invest in the physical infrastructure of the enterprise, the private entity manages the public service and receives therefore be users (sponsored concession) to be exclusively the Government (administrative concession). In the case of prisons, the PPP mode is the administrative concession. Although the debate regarding the PPP in the prison system is still at the beginning, the State of Minas Gerais, in the city of Ribeirão das Neves, lives the first Brazilian experience. What is clear from mining example, is that PPP's are a plausible reality to provide the prisoner dignity, respect the law, and especially the possibility of being reinserted into society through study and work. Regarding legality, Federal Law n. 11.079 / 2007 and the Tocantins State Law n. 2231/2009 authorizing the deployment of PPP's in the prison system. In the same turn, there is constitutional because it is not delegating the execution of the sentence, but only the management of prisons. Regarding the economic viability, the novel model brings savings for the state and generates profit to the partner. On social benefits, these are immeasurable because they allow a greater rehabilitation rate, less recurrence, and by corollary, results in reduced crime rate. In the state of Tocantins, although the prison population is low, there is also overcrowding. 3,233 are imprisoned for 2,284 vacancies, that is intended to change the Tocantins prison reality, the implementation of the PPP would be an effective alternative to end deficit of vacancies and comply with the provisions of the Prison Law.